Social report 2024 Arcigay (European journal of volunteering and community-based projects, 2025)
With this Social Report, they aimed to highlight the activities carried out by Arcigay throughout 2024, from projects of national relevance and impact to the multitude of local initiatives and programs that represent the true backbone of the association. To measure and effectively communicate the impact of their actions, they relied on the framework offered by the United Nations’ 2030 Agenda, seeking to present their results in relation to the Sustainable Development Goals.This publication represents the fifth voluntarily produced Social Report by Arcigay, reaffirming their commitment to transparency, dialogue, and accountability toward all stakeholders. The drafting of this document stems from the intention to provide a clear and accessible overview of the value generated not only economically, but above all socially. Although voluntary in nature, the Report aims to meet the requirements established for Third Sector organizations, while maintaining a “POP” communication approach, meaning more readable, inclusive, and accessible to the diverse audiences that engage with Arcigay.
Keywords: social report; arcigay